2015
DOI: 10.1261/rna.052696.115
|View full text |Cite
|
Sign up to set email alerts
|

Poly(U) RNA-templated synthesis of AppA

Abstract: Simple nucleotide templating activities are of interest as potential primordial reactions. Here we describe the acceleration of 5 ′ -5 ′ AppA synthesis by 3 ′ -5 ′ poly(U) under normal solution conditions. This reaction is apparently templated via complementary U:A base-pairing, despite the involvement of two different RNA backbones, because poly(U), unlike other polymers, significantly stimulates AppA synthesis. These interactions occur in moderate (K + ) and (Mg 2+ ) and are temperature sensitive, being more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…Thus the chemical reaction is second order overall in the nucleotides, and the GppG-stimulated reaction is third order overall: first order in two A nucleotides plus first order in GppG. This resembles previous cross-templated reactions, which behave in a similar second-and third-order fashion overall (Puthenvedu et al 2015;Majerfeld et al 2016). …”
Section: Reaction Order For the Putative Templatesupporting
confidence: 73%
See 4 more Smart Citations
“…Thus the chemical reaction is second order overall in the nucleotides, and the GppG-stimulated reaction is third order overall: first order in two A nucleotides plus first order in GppG. This resembles previous cross-templated reactions, which behave in a similar second-and third-order fashion overall (Puthenvedu et al 2015;Majerfeld et al 2016). …”
Section: Reaction Order For the Putative Templatesupporting
confidence: 73%
“…The lane marked "0" is an unincubated complete reaction, "inc" is the untemplated reaction after 19 h at 12°C, and "inc + GppG" implies the same incubation but with 10 mM GppG added. This is the chromatographic system previously used for detection of AppA (Puthenvedu et al 2015), and the identity of the product has been confirmed by HPLC (D Puthenvedu and M Yarus, in prep.). By determining the fraction of total radioactivity in the product spot, product concentration can be calculated from known total [pA].…”
Section: Measurement Of Productsmentioning
confidence: 83%
See 3 more Smart Citations